MORAL HARASSMENT AT WORK OF CARE PROFESSIONALS FOR VICTIMS OF VIOLENCE AGAINST WOMEN - Andrade Santos, Karine David; Silva, Joilson Pereira da; Cantera Espinosa, Leonor María (Revista Valore, 2024)
This research aimed to describe the moral harassment at work experienced by care professionals for victims of violence against women. For this project, this study was structured with a qualitative design, involving 12 care professionals for victims of violence against women in different care centers for these clients in the interior of Sergipe, Brazil, who were submitted to an interview script on moral harassment aspects. These interviews were recorded and transcribed, followed by the application of content analysis according to Bardin. The results found five categories of moral harassment in the following aspects: practices, authors of abusive behaviors, situations of violence in the workplace and consequences for the worker. The professionals surveyed experienced the following moral harassment practices: devaluation, defamation and intimidation that materialized in the execution of the tasks, time of arrival and departure from work, formal and informal meetings, decision making and fundraising for work activities. These abusive behaviors were carried out by the hierarchical superiors and entailed consequences for physical and mental health and, mainly, for the work motivation of the harassed. Thus, in view of the results found, it is fundamental to implement preventive and intervention strategies aimed at moral harassment in these spaces.